Plant DNA Polymerases - Pedroza-Garcia, Jose-Antonio (Int J Mol Sci, 2019)
Maintenance of genome integrity is a key process in all organisms. DNA polymerases (Pols) are central players in this process as they are in charge of the faithful reproduction of the genetic information, as well as of DNA repair. Interestingly, all eukaryotes possess a large repertoire of polymerases. Three protein complexes, DNA Pol α, δ, and ε, are in charge of nuclear DNA replication. These enzymes have the fidelity and processivity required to replicate long DNA sequences, but DNA lesions can block their progression. Consequently, eukaryotic genomes also encode a variable number of specialized polymerases (between five and 16 depending on the organism) that are involved in the replication of damaged DNA, DNA repair, and organellar DNA replication. This diversity of enzymes likely stems from their ability to bypass specific types of lesions. In the past 10–15 years, our knowledge regarding plant DNA polymerases dramatically increased. In this review, we discuss these recent findings and compare acquired knowledge in plants to data obtained in other eukaryotes. We also discuss the emerging links between genome and epigenome replication.